METODE SQ3R PADA PEMAHAMAN TEKS EKSPLANASI: STRATEGI PENINGKATAN PEMAHAMAN SISWA MENENGAH PERTAMA - Aini, Hajarul; Syahputra, Mulyadi (Jurnal Metrum, 2025)
The aim of this study is to describe the implementation of specific steps of SQ3R which can improve the students’ ability in comprehending explanation text and to describe the improvement of students’ ability in comprehending the explanation text. This study was conducted at SMPN 8 Banda Aceh. The background of this study is based on the students’ problem in comprehending the text in English and their difficulties in expressing the idea of the text in a complete, coherent and systematic summary. This study used descriptive qualitative method in analyzing the data. Based on the result of two cycles done at second year students of SMPN 8 Banda Aceh, there is an improvement in students’ ability in comprehending the explanation text. In the first cycle tehe result shows that the students summary which gained 80 or more (KKM) is 66,66% while the second cycle the percentage of students who a chieved the score 80 or more (KKM) is 95,45. It can be concluded from the result of both cycles that implemantation of SQ3R can improve the students ability in comprehending the explanation text at SMPN 10 Banda Aceh.